2011
DOI: 10.3945/ajcn.111.018366
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of added sugars is decreasing in the United States

Abstract: Although the consumption of added sugars in the United States decreased between 1999-2000 and 2007-2008, primarily because of a reduction in soda consumption, mean intakes continue to exceed recommended limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
312
5
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(346 citation statements)
references
References 19 publications
23
312
5
6
Order By: Relevance
“…This is 5·7 g/d higher than our findings from the 2011-2012 NNPAS, but the percentage energy from added sugar is similar between the two surveys. Studies from other developed countries also report a declining trend in added sugar consumption (16,18,34,35) . For example, using data from the National Health and Nutrition Examination Survey (NHANES) in the USA, Welsh et al (16) observed a 23·4 g/d decrease in added sugar intake between 1999-2000 and 2007-2008 among US residents aged 2 years or above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is 5·7 g/d higher than our findings from the 2011-2012 NNPAS, but the percentage energy from added sugar is similar between the two surveys. Studies from other developed countries also report a declining trend in added sugar consumption (16,18,34,35) . For example, using data from the National Health and Nutrition Examination Survey (NHANES) in the USA, Welsh et al (16) observed a 23·4 g/d decrease in added sugar intake between 1999-2000 and 2007-2008 among US residents aged 2 years or above.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other developed countries also report a declining trend in added sugar consumption (16,18,34,35) . For example, using data from the National Health and Nutrition Examination Survey (NHANES) in the USA, Welsh et al (16) observed a 23·4 g/d decrease in added sugar intake between 1999-2000 and 2007-2008 among US residents aged 2 years or above. However, the magnitude of change observed was larger, possibly due to the higher intake reported in the earlier NHANES (100·1 g/d), leaving more room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…India, East Asia and Latin America continue to drive growth in world sugar consumption and the FAO predicts an increase of about 2?0 % per annum over the next decade (14,15) . Conversely, per capita sugar consumption in developed countries has continued to decline in the past decade, probably related to health concerns and near saturation of the sugar and sweetener markets (16)(17)(18) . However, per capita sugar consumption in developed countries remains high and, according to recent estimates, it may account for .20 % of the total energy ingested by some individuals (19)(20)(21) .…”
mentioning
confidence: 99%
“…[3][4][5][6][7] Evidence suggests that the consumption of sugarsweetened beverages (SSBs) has increased in parallel to overweight and obesity trends. [8][9][10][11] Currently, SSBs contribute between 10% and 15% of youth's caloric intake and are the primary source of added sugar in the diet of children and adolescents. 12 Approximately 25% of US adolescents consume more than 750 mL of SSBs per day, which represents more than 350 calories.…”
Section: Introductionmentioning
confidence: 99%